Preoperative magnetic resonance spectroscopy improves diagnostic accuracy in a series of neurosurgical dilemmas. (October 2013) - Rao, P. J.; Jyoti, R.; Mews, P. J.; Desmond, P.; Khurana, V. G.
Abstract Object. The purpose of this study was to evaluate the usefulness of preoperative magnetic resonance spectroscopy (MRS) in neurosurgical patients with diagnostically challenging intracranial lesions. Methods. Included in this study are twenty-three consecutive patients presenting to the neurosurgery service with diagnostically challenging intracranial lesions and who were investigated by conventional MR imaging and proton (1H) MRS, followed by surgery with subsequent histopathological diagnosis. An experienced neuroradiologist (RJ) blinded to the final histopathology evaluated the imaging studies retrospectively. Provisional diagnoses based on preoperative clinical and conventional MR data versus preoperative MRS data were compared with definitive histopathological diagnoses. Results. Compared with preoperative clinical and conventional MR data, 1H MRS improved the accuracy of MR imaging from 60.9% to 83%. We found 1H MRS reliably distinguished between abscess and high-grade tumour, and between high-grade glioma and low-grade glioma, but was not able to reliably distinguish between recurrent glioma and radiation necrosis. In 12/23 cases (52%) the 1H MRS findings positively altered our clinical management. Two representative cases are presented. Conclusions. Our study supports a beneficial role for 1H MRS in certain diagnostic intracranial dilemmas presenting to neurosurgeons. The information gleaned from preoperative 1H MRS can be a useful adjunct to clinical and conventional MR imaging data in guiding the management of patients with intracranial pathologies, particularly high-grade tumour versus abscess, and high-grade versus low-grade glioma. Further larger prospective studies are needed to clearly define the utility of 1H MRS in diagnostically challenging intracranial lesions in neurosurgery.